Clinical evaluation of DSL-BCD fittings: assessing output-to-targets for percutaneous bone conduction devices in practice - Gascon, Alex; Bagatto, Marlene; Scollie, Susan; Cowan, Cassandra; Hodgetts, William (Frontiers in Audiology and Otology, 2025)
ObjectivesObjective measurements and prescriptive formulas for air-conduction hearing aids have been discussed extensively in the literature. In contrast, the application of objective verification tools such as clinical skull-simulators in the bone-conduction amplification literature is still emerging. This approach offers a critical step toward understanding the variability in percutaneous bone-conduction hearing devices (BCD) output on a larger scale. Our study aims to quantify this variability using skull-simulator measurements of percutaneous BCD users, thereby generating accuracy description of the range of outputs normally fitted in a clinical context.DesignA cross-sectional retrospective study was conducted, analyzing skull-simulator measurements from routine audiology appointments of 79 adult percutaneous BCD users fitted with the DSL-BCD v1.1 prescription procedure. We explored the relationship between in-situ bone-conduction hearing thresholds and frequency-specific and root mean square error (RMSE) deviations from targets, along with aided speech intelligibility index (SII) using linear regressions for standard speech signals. BCD skull-simulator measurements were conducted at the user's daily listening level.ResultsAt a 65 dB SPL speech input, over 50% of participants showed output-to-target deviations within ±5 dB at all frequencies except 750, 6,000, and 8,000 Hz. Fittings generally fell below targets as in-situ bone-conduction thresholds worsened, with exceptions at 250 and 500 Hz showing the reverse trend. A significant correlation was observed between in-situ bone-conduction thresholds and aided SII across all input levels, indicating an expected decrease in aided SII with increased bone-conduction hearing loss. The RMSE was within 5 dB for 37% of participants, lower than reported in air-conduction hearing aid literature. Secondary analyses assessing BCD capabilities of matching targets following fine-tuning, without participants' involvement, indicated that a RMSE within 5 dB could be met in 79% of cases.ConclusionsThis study outlines the deviations in output-to-target and aided SII among adult percutaneous BCD users, offering clinicians a benchmark through 95% confidence interval regression models and in-situ threshold averages. This normative data is beneficial for fitting BCDs in users with elevated in-situ thresholds, reducing uncertainty about optimal fittings. Further research is necessary to elucidate the relationship between aided SII, output-to-target deviations, outcomes and preferences in percutaneous BCD wearers.